Bank nationalization and the Supreme Court judgment - Singhvi, L. M. (ed.) (Delhi, 1971)
The Parliament and the State Legislatures enact legislation within the ambit and sphere of their legislative power. Frequen tly the High Courts and the Supreme Court are called upon to interpret the laws and to examine their validity. The power to interpret legislation, to review it and to pass on its validity or otherwise is a crucial power vested in the higher judiciary for securing orderly government. When the Legislature legislates, it performs a function which is confided to it by the Constitu tion; when the Supreme Court finally interprets a piece or provi sion of legislation and gives its verdict on its validity or other wise, it finally determines the status, effect and meaning of the enactment and its various provisions. The verdict of the Supreme Court may or may not meet with the approval or the concur rence of the other organs of Government or that of public opi nion. The point is that in the democratic process under a written Constitution, there should be proper comity between the diffe rent organs of the Government. It is in this context that the judgment of the Supreme Court in the Bank Nationalization case may appropriately be discussed. Within the limits of pro priety and with all due respect for the Supreme Court, it is quite permissible for us to try and understand what the Supreme Court has laid down, what the judgment implies, what its repercussions are likely to be and how consistent and rational that pronouncement is. Implicit respect for the judiciary is an obligation of civilized citizenship. It does not however take away the right of the citizen or the legislator to make fair, informed and concerned comments on judicial decisions.
Keywords: Banks and banking India